The Role of Marketing in Building An Environmental Agenda: Reflections A Case Study of One From the Public Management (Revista Brasileira Multidisciplinar, 2010)
This paper – a case study discusses – the construction of an environmental agenda in a public managing relating this process to the marketing used in the city of Catanduva, São Paulo state. Its aim is to evaluate the importance of the use of techniques and communication methods as mechanisms of human interaction related to environmental questions and if hiring a marketing agency has produced some changes in the people. With this aim, a series of researches was developed based on the register of the environmental campaigns promoted by the Water and Sewage Treatment Sector of Catanduva (Superintendência de Água e Esgoto de Catanduva – Saec) with the main involved actors: the communication agency, the local public power, and later, the people and the opinion formers in the city. The adopted methodology involved consulting the Saec data about water consume in the periods which preceded and succeeded the environmental campaigns which took place in Catanduva and questionnaires applied in two sections of the city, with different socioeconomic composition.We also interviewed public management agents, who were directly or indirectly involved in the environmental question, section leaders, among others. This way it was possible to verify that public local policies frequently use marketing to help in the conduction of environmental awareness processes, but, unluckily, the process is still deficient and great part of the actions doesn't reach their primary objectives. It is possible to conclude that local public policies, even using marketing, have made little progress in making citizens aware of the necessities of habit changes in environmental issues.
Keywords: Environment; Local public policies; Environmental marketing; Local environmental awareness; Management of Catanduva.